Exact solutions for bimorph cross-ply and antisymmetric angle-ply plate piezoelectric energy harvesters. (15th April 2022) - Ray, M.C.; Jha, B.K.
Abstract: This paper presents the exact solutions for the plate type piezoelectric bimorph energy harvesters composed of laminated cross-ply or angle-ply substrate plate. Both series and parallel connections of the piezoelectric layers of the bimorphs are considered for deriving the exact solutions. Since the exact solutions for the layers of the laminated substrate plate are available in the open literature exact solutions for the piezoelectric layers are only derived here for finding the exact solutions of the harvesters. The piezoelectric layers should be orthotropic or generally orthotropic for deriving the exact solutions. Three sets of exact solutions for the piezoelectric layers are required to be derived. The electric potential induced by the bimorph in which the piezoelectric layers are connected in series is significantly larger than that in case of the bimorph with piezoelectric layers connected in parallel. The effects of the variations of the off-axis angle in the generally orthotropic piezoelectric layer, the length over width ratio of the harvester and the thickness of the piezoelectric layers on the induced electric potential have been studied. The expressions for the exact solutions can be used in a straight forward manner for verifying the experimental and the numerical results.